Effect of early childhood cow's milk elimination diet on eating behaviours, nutrition and growth status at age 2–6 years. Issue 2 (16th June 2021) - Ercan, Nazli; Tel Adıgüzel, Kübra
Abstract: Background: The present study aimed to investigate the eating behaviour, nutritional status and growth of Caucasian children in ages 2–6 years who had a diet because of cow's milk protein allergy (CMA) [immunoglobulin (Ig)E‐mediated and/or non‐IgE‐mediated] in early childhood. Methods: In this cross‐sectional, case–control study, the cow's milk elimination (CME) group comprised children aged 0–2 years who were receiving a CME diet because of CMA, as confirmed by an oral food challenge test, and had reintroduced cow's milk for at least ≥ 3 months. The control group never had a restricted diet. Eating behaviour and children's growth was assessed. A 3‐day food record was taken to determine the macronutrient and micronutrient intake of the children. Data on the children's socio‐demographic, infant nutrition and family allergy history were collected from their medical records and face‐to‐face interviews with mothers. Results: In total, 62 children with a median age of 32 months were recruited for the study. The total scores of food avoidance and satiety responsiveness in the CME group (n:31) were higher than in the controls ( n  = 31) ( p  = 0.036 and 0.006, respectively). Weight‐for‐age and height‐for‐age are statistically lower in the CME group than in the control group ( p  < 0.001). A significant difference between groups in terms of dairy intake was recorded ( p  = 0.011). In the CME group, the current frequency of adequate energy, vitamin B1, folic acid, vitamin C and calcium intake was significantly lower than in the control group ( p  < 0.05). Conclusions: Dietary interventions because of CMA at age 0–2 years can affect children's nutritional habits and parental‐reported assessment of children's eating behaviours, resulting in growth restriction with insufficient micro/macronutrients and/or dairy products at the age of 2–6 years. Abstract : The present study set out to demonstrate the difference in children's eating behaviour who had a CME diet because of CMA (Ig E‐mediated and/or non‐Ig E‐mediated) in early childhood and the effects of these changes in children's eating behaviours on their future nutritional and growth status. The study results showed that dietary interventions at 0–2 years of age for CMA (elimination diet and/or substitute formula use) had an unintended impact on the children's eating behaviours and their growth during 2–6 ages. In addition, in the CME group, the longer children are on a CME diet, the less their intake of dairy products at 2–6 years of age, which leads to an inadequate intake of some macro/micronutrients.